2014
DOI: 10.1139/cjz-2014-0010
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of gross composition, energy value, and fatty acid profile of milk from lowland tapir (Tapirusterrestris) during different lactation periods

Abstract: We evaluated gross composition, energy value, and fatty acid profile of colostrum, transitional, and mature milk of lowland tapir (Tapirus terrestris (L., 1758)) from Argentina. Samples were obtained from six healthy animals kept in captive or semicaptive conditions. Protein content varied over time from 6 to 19 g/100 g of milk; carbohydrates varied from 2.4 to 5.4 g/100 g of milk; fat varied from 2.4 to 17.3 g/100 g of milk. Energy value also varied over time, with colostrum having the highest value. Fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…In general, rhinoceros milk contains lower amounts of fat, higher lactose and equal protein compared to the Equidae, while the Tapiridae milk contains the highest amounts of fat and protein, and lowest lactose. Compositional changes in milk of rhinoceroses over lactation are very small compared to that of the Equidae (Salimei & Fantuz, 2012) and Tapiridae (Van Nieuvenhove et al 2014).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…In general, rhinoceros milk contains lower amounts of fat, higher lactose and equal protein compared to the Equidae, while the Tapiridae milk contains the highest amounts of fat and protein, and lowest lactose. Compositional changes in milk of rhinoceroses over lactation are very small compared to that of the Equidae (Salimei & Fantuz, 2012) and Tapiridae (Van Nieuvenhove et al 2014).…”
Section: Resultsmentioning
confidence: 96%
“…The GE of the white rhinoceros was 47.26 ± 5.12 kCal/100 g milk, which was 10 kCal higher than that of the Indian (Gimmel et al, 2018) and black rhinoceros (Gregory et al, 1964). Available data indicated that the lowland tapir had double the GE (Van Nieuvenhove et al 2014), with the Equidae displaying levels in‐between those of the rhinoceros and tapir.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Individual fatty acids were identified through the use of a standard mixture (37‐component fatty acid methyl esters [FAME] mixture; Supelco Inc., Bellefonte, PA, USA) of fatty acids run at the time of instrumental analysis. Results were transformed into percentage of total fatty acids for analysis, following the methods of similar studies (Pavithra, Gowda, Rajesh Kumar, Prasanna, & Shivanna, 2012; Stefanova, Toshkov, Vasilev, Vasilev, & Marekov, 2011; Van Nieuwenhove, Perez, Hernandez, & Luna Pizzaro, 2014).…”
Section: Methodsmentioning
confidence: 99%